2021
DOI: 10.1021/acsbiomaterials.0c01286
|View full text |Cite
|
Sign up to set email alerts
|

Biogenesis of Extracellular Vesicles Produced from Human-Stem-Cell-Derived Cortical Spheroids Exposed to Iron Oxides

Abstract: Stem-cell-derived extracellular vesicles (EVs) are promising tools for therapeutic delivery and imaging in the medical research fields. EVs that arise from endosomal compartments or plasma membrane budding consist of exosomes and microvesicles, which range between 30 and 200 nm and 100–1000 nm, respectively. Iron oxide nanoparticles can be used to label stem cells or possibly EVs for magnetic resonance imaging. This could be a novel way to visualize areas in the body that are affected by neurological disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 60 publications
1
36
0
Order By: Relevance
“…In this ScR, we found that the variety of NMs exposed to the different biological models increased exosome secretion (see Figure 3 B), whereas no significant differences were observed regarding their size or morphology [ 26 , 39 , 40 , 41 , 44 , 45 , 46 , 49 , 51 ]. Many studies reported vesicles with a cup-shaped appearance in the negative-stain TEM with HSP 70, CD63, CD81, CD9, LAMP1, and TSG101 as characteristic markers, suggesting that the vesicular secretome that was isolated also comprised exosomes.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…In this ScR, we found that the variety of NMs exposed to the different biological models increased exosome secretion (see Figure 3 B), whereas no significant differences were observed regarding their size or morphology [ 26 , 39 , 40 , 41 , 44 , 45 , 46 , 49 , 51 ]. Many studies reported vesicles with a cup-shaped appearance in the negative-stain TEM with HSP 70, CD63, CD81, CD9, LAMP1, and TSG101 as characteristic markers, suggesting that the vesicular secretome that was isolated also comprised exosomes.…”
Section: Discussionmentioning
confidence: 88%
“…Regarding the physicochemical characteristics of NMs, 78% of studies used nanoparticles of different chemical compositions as test substances (e.g., metallic, polymeric, metallic oxides, inorganic, etc.) [ 24 , 40 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. The remaining studies used nanotubes, nanoclusters, nanosheets, as well as dendrimers [ 26 , 49 , 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations